Smart Innovations in Communication and Computational Sciences Proceedings of ICSICCS-2018 - Tiwari, Shailesh; Trivedi, Munesh C.; Mishra, Krishn K.; Misra, A. K.; Kumar, Khedo Kavi.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
The book presents the latest advances and research findings in the fields of computational science and communication. The areas covered include smart innovation; systems and technologies; embedded knowledge and intelligence; innovation and sustainability; advanced computing; and networking and informatics. It also focuses on the knowledge-transfer methodologies and the innovation strategies employed to make these effective. This fascinating compilation appeals to researchers, academics and engineers around the globe.
1. Design of Eye Template Matching Method for Head Gesture Recognition System -- 2. Real time Meta learning approach for Mobile Healthcare -- 3.Firearm Detection from Surveillance Cameras Using Image Processing and Machine Learning Techniques -- 4. Segmentation of Optic Disc by Localized Active Contour model in Retinal Fundus Image -- 5. A Novel Genetic Algorithm Based Scheduling for Multi-core Systems -- 6.Various Pre-Processing Methods for Neural Network based Heart Disease Prediction -- 7. Intelligent Passenger Information System using IoT for Smart Cities -- 8. Continuous Monitoring and Detection of Epileptic Seizures using Wearable Device -- 9.Brain Tumor Detection Using Cuckoo Search Algorithm and Histogram Thresholding for MR Images -- 10.eMDPM: Efficient Multi-dimensional pattern Matching algorithm for GPU -- 11. Computer vision-based fruit disease Detection and classification.
Keywords: Computational intelligence; Telecommunication; Artificial intelligence; Computational Intelligence; Communications Engineering, Networks; Artificial Intelligence